The Escherichia coli divisome: born to divide. (20th August 2013) - Natale, Paolo; Pazos, Manuel; Vicente, Miguel; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary Septation in Escherichia coli involves complex molecular mechanisms that contribute to the accuracy of bacterial division. The proto‐ring, a complex made up by the FtsZ, FtsA and ZipA proteins, forms at the beginning of the process and directs the assembly of the full divisome. Central to this complex is the FtsZ protein, a GTPase able to assemble into a ring‐like structure that responds to several modulatory inputs including mechanisms to position the septum at midcell. The connection with the cell wall synthesising machinery stabilizes the constriction of the cytoplasmic membrane. Although a substantial amount of evidence supports this description, many details on how individual divisome elements are structured or how they function are subjected to controversial interpretations. We discuss these discrepancies arising from incomplete data and from technical difficulties imposed by the small size of bacteria. Future work, including more powerful imaging and reconstruction technologies, will help to clarify the missing details on the architecture and function of the bacterial division machinery.